A infraestrutura de transportes rodoviários no Brasil e as trilhas da financeirização - Peruchi, Paulo Renato (Universidade Federal de São Carlos, 2020)
The present work has as main objective to understand how changes in the investment model in road transport infrastructure, implemented since the 1990s, impacted organizations working in the sector. For this purpose, a historical analysis was made and the trajectory of the road infrastructure sector was studied, in order to understand the changes in the investment model, and the resulting organizational impacts. The change in the investment model reflects the decrease in State participation and the use of highway concessions and public private partnerships (PPPs) as an alternative. Theoretical support for the analyzes was provided by elements of economic sociology, which provided an interdisciplinary approach and added new elements to the study, in opposition to the traditional approaches of a purely economic nature carried out until then. The analyzes carried out indicate that organizations responded to changes in the investment model through the incorporation of elements of the financial logic to direct their activities, and changes in their structures, facts that contributed to activities that are not necessarily related to the productive sphere gain relevance and help build a new way of “thinking” the sector, marked by its movement towards financialization, impacting organizations, and interactions between organizations, the State and markets.
Road transport infrastructure in Brazil and the financialization trails
Keywords: Financeirização; Lógica financeira; Infraestrutura de transportes rodoviários; Sociologia econômica; Estudos organizacionais; Financialization; Financial logic; Road transport infrastructure; Economic sociology; Organizational studies; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO